2011
DOI: 10.1517/14728222.2011.585971
|View full text |Cite
|
Sign up to set email alerts
|

Biology and novel treatment options for XLA, the most common monogenetic immunodeficiency in man

Abstract: Work from various laboratories demonstrates the feasibility of using gene-corrected HSCs to complement the immune defects of Btk-deficiency in mice. We propose that it is timely to start clinical programs to develop stem cell based therapy for XLA, using gene-corrected autologous HSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 151 publications
0
47
0
2
Order By: Relevance
“…2 BTK comprises 5 structural domains, including pleckstrin homology, TEC homology, Src homology 2 and Src homology 3, and kinase domains 3 ; full BTK kinase activation is dependent on recruitment to the plasma membrane via the pleckstrin homology domain following phosphatidylinositol (3,4,5) triphosphate binding. 4 In humans, BTK mutations result in arrested B-cell development leading to severe agammaglobulinemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 BTK comprises 5 structural domains, including pleckstrin homology, TEC homology, Src homology 2 and Src homology 3, and kinase domains 3 ; full BTK kinase activation is dependent on recruitment to the plasma membrane via the pleckstrin homology domain following phosphatidylinositol (3,4,5) triphosphate binding. 4 In humans, BTK mutations result in arrested B-cell development leading to severe agammaglobulinemia.…”
Section: Introductionmentioning
confidence: 99%
“…4 In humans, BTK mutations result in arrested B-cell development leading to severe agammaglobulinemia. 5 This, along with the observations of the central role of BTK in signaling from the B-cell receptor, has indicated that BTK is a functional therapeutic target and has led to the development of small-molecule BTK inhibitors for the treatment of B-cell malignancies and autoimmune conditions. 6 An interesting feature of the adenosine triphosphate-binding pocket of BTK is the presence of a cysteine residue at 481; only 9 other kinases retain cysteine at comparable sites.…”
Section: Introductionmentioning
confidence: 99%
“…A pathogenic role for BTK in rheumatic diseases is further emerging from mouse studies demonstrating that smallmolecule BTK inhibitors prevent or ameliorate lupus nephritis and experimental arthritis (25)(26)(27)(28)(29)(30)(31). However, BTK inhibitors are likely to have effects beyond BCR signaling, because BTK functions downstream of many receptors, including chemokine and TLRs, and is also expressed in myeloid cells (32). Apart from direct effects on BTK-expressing cells, BTK inhibition was associated with diminished activation of both helper and cytotoxic T cells (25), raising the question how these T cells are indirectly activated in a BTK-dependent manner.…”
mentioning
confidence: 99%
“…[11][12][13] The defects in murine Btk-deficient B cells range from reduced responsiveness to BCR and Toll-like receptor (TLR) stimulation to decreased signaling of chemokine receptors. 14 Several lines of evidence indicate that Btk expression levels may present the rate-limiting step in BCR signaling and that tight regulation of Btk expression and kinase activity is essential for normal B-cell development and activation. Firstly, expression of subphysiologic levels of transgenic Btk only partially corrects the phenotype of Btk-deficient B cells, 15 whereas physiologic levels fully rescue this phenotype.…”
mentioning
confidence: 99%